Guía para diseño integral de sistemas de distribución de gas natural para edificaciones residenciales, comerciales e industriales (2017)
Guide to the design of natural gas networks in residential, commercial and industrial buildings, focused on Colombian regulations. This document mentions the basic concepts that must be taken into account for gas designs in medium and low pressure in buildings.